Estudo do papel da proteína eIF5A na elongação da tradução em S. cerevisiae: análise da relação funcional com o trna de alanina e sua participação na síntese proteica geral da célula - Watanabe, Tatiana Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
eIF5A is highly conserved between archaea and eukaryotes and has a unique and essential postranslational modification, called hypusination. eIF5A was initially described as a translation initiation factor (eukaryotic Initiation Factor 5A) but it was shown that eIF5A engaged in translation elongation. Recently findings demonstrated that eIF5A is most important for specific translation of proteins containing consecutive proline residues. In order to deepen the knowledge of function of eIF5A during the translation process, this research studied the functional correlation between eIF5A and the alanine tRNA (tRNAAla), revealed as a genetic interaction in Saccharomyces cerevisiae, and also evaluated the effect of eIF5A in events of protein synthesis as Programmed Ribosomal frameshifting (PRF), misincorporation and readthrough using dual luciferase reporters. First, the allele specificity of the high copy suppression caused by tRNAAla and the ability of tRNAs for other amino acids to suppress the growth of eIF5A mutants were analyzed, and the results showed that this deletion does not occur in an allele specific manner and interestingly, among other tRNAs tested, only tRNAiMet is able to suppress the growth phenotype of the eIF5A mutant tif51AK56A. The suppression induced by these tRNAs does not reflect in improvement of the mutant defect in polysomal profile, for both cases. It was also tested direct physical interaction between eIF5A and tRNAAla using three-‐hybrid system, however, no interaction was detected, suggesting that the interaction observed between eIF5A and tRNA in the 80S complex is dependent on the ribosome. The Programmed Ribosomal frameshifting (PRF) experiments showed an increase in PRF numbers for the signals of the virus LA and HIV-‐1 in eIF5A mutant strains, demonstrating that eIF5A function interferes with mRNA recoding events. Furthermore, the same mutants showed an increase...

eIF5A é uma proteína altamente conservada entre arqueas e eucariotos e apresenta uma modificação pós-‐traducional única e essencial para sua função, chamada de hipusinação. eIF5A foi inicialmente identificado como um fator de início de tradução (eukaryotic translation Initiation Factor 5A) porém foi demonstrado que eIF5A atua na elongação da tradução. Recentemente foi demonstrado que eIF5A seja mais importante na tradução específica de proteínas contendo resíduos consecutivos de prolina. No intuito de aprofundar o conhecimento da participação de eIF5A no processo de tradução, o presente trabalho de doutorado estudou a relação funcional entre eIF5A e o tRNA de alanina (tRNAAla), revelada como uma interação genética em Saccharomyces cerevisiae, assim como avaliou a relação de eIF5A com eventos da síntese proteica como Programmed Ribosomal Frameshifting (PRF), misincorporation e readthrough, utilizando repórteres de duas luciferases. Primeiramente, foi analisada a especificidade alélica da supressão em alto número de cópias ocasionada por tRNAAla e a capacidade de tRNAs para outros aminoácidos suprimirem o fenótipo de crescimento de mutantes de eIF5A, e os resultados mostraram que esta supressão não se dá de maneira alelo específica e curiosamente, dentre os outros tRNAs testados, apenas o tRNAiMet é capaz de suprimir o fenótipo de crescimento do mutante tif51AK56A de eIF5A. A supressão observada por estes tRNAs não reflete na melhora do defeito no perfil polissomal, para ambos os casos. Foi testada também a interação física direta entre eIF5A e o tRNAAla, utilizando o sistema de triplo-‐híbrido, no entanto, nenhuma interação foi detectada, sugerindo que a interação observada entre eIF5A e o tRNA em complexo com 80S seja dependente do ribossomo. Os experimentos de Programmed Ribosomal Frameshifting (PRF) revelaram um aumento na taxa de PRF para...
Keywords: Proteinas - Sintese; Ribossomos; Saccharomyces cerevisiae; Acido ribonucleico; Proteínas; Proteins